Exploratory Space for Whom? Children’s Opportunities for Subject-Related Learning in Early Childhood Education and Care - Maria Rönnlund; Sofie Areljung; Anna Günther-Hanssen; Mia Heikkilä; Carina Hjelmér; Anna Lindqvist; Annika Manni (Nordic Studies in Education)
In this article we explore how children’s opportunities for subject-related learning in Nordic early childhood education and care (ECEC) depend on intra-actions between the physical environment, gender norms, and the relevant learning content. We apply a socio-material perspective and draw on three Swedish ECEC studies, in which the learning content was related to physics, dance, and environmental sustainability, respectively. The analyses illustrate how socio-material intra-actions encouraged or impeded certain bodily encounters, thereby encouraging or impeding certain kinds of subject-related learning.